Pengaruh Latihan Mirror Neuron System Terhadap Peningkatan Kemampuan Fungsional Anggota Gerak Atas Pada Pasien Pasca Stroke - ENIRAHMAWATI, ENIRAHMAWATI, Dwi Rosella K, S.St FT., M.Fis, Yulisna Mutia Sari, SSt.FT., M.Sc () (2015)
Stroke is a vascular disease were classified as ischemic and hemorrhagic with 3 phases: acute, sub-acute and chronic. Each stroke will leave residual symptoms may include weakness and even paralysis until the recovery phase. One problem that often arises in patients with stroke recovery phase is a decrease in functional ability limb. In this case physiotherapy has the form of exercise intervention Mirror Neurons System Excercise used to improve the functional capabilities upper limbs in patients with post stroke. This population study amounted to 10 people, 6 people in the village and the rest in Ngringun Pandanan beautiful with sample are 2 people. This research uses descriptive qualitative research design, with a single case study research method with a mirror exercise independent variables and the dependent variable system functional capabilities upper limbs. Both the respondent will be given mirror neuron system exercises as much as 2 times a week for 1 month with duration of exercise for 40 minutes to 1 hour. Exposure results in this study were made in the form of data description, namely in the form of results: functional ability as measured using the Wolf Motor Function Test (WMFT) are presented in graphical form that will be measured every week for each patient. The results showed an increase in both the respondents, respectively an increase of 37.3% and 32%. It was concluded that the mirror neuron system practice has the effect in improving functional ability